Headspace solid-phase microextraction for the recovery of petroleum based accelerants in fire debris - 561482 Umi Kalthom Ahmad; Chin, K. Voon; Loi, T. Sek; Indo-Pacific Congress on Legal Medicine and Forensic Sciences (7th : 2001 : Melbourne) (Skudai : Universiti Teknologi Malaysia, 2001)
42